180k views
0 votes
Let A = R − {−2}, B = R − {1} and f : A → B be given by the rule f(x) = x + 1 x + 2 . (a) Prove f is one-to-one. (b) Prove f is onto B. (Comment: don’t forget that if given b ∈ B, you construct a such that f(a) = b, you must also show a ∈ A.)

User Tourki
by
6.0k points

1 Answer

5 votes

Step-by-step explanation:

In order to prove that f is one-to-one and surjective, we can prove directly that f is bijective by findng
f^(-1) .


f(x) = (x+1)/(x+2)

To calculate the inverse of f, first we swap the variables x and y. Then we write y in values of x.


x = (y+1)/(y+2)


x/(y+2) = y+1


xy +2x = y+1

On this step it is important to separate what terms contain y and what terms do not. After that we can separate y as a factor


2x = y+1 -xy


2x-1 = y-xy


2x-1 = y(1-x)


y = (2x-1)/(1-x)

Thus,
f^(-1)(x) = (2x-1)/(1-x) . Note that
f^(-1) is well defined en every element of B, because it can be defined on any element different from 1, where the divider is zero.

An element of the form
(2x-1)/(1-x) , for some x, is an element of A because it is different from -2. Lets suppose that there exist an x such as
(2x-1)/(1-x) = -2 , thus 2x-1 = -2(1-x) = -2+2x, from where we conclude that 0 = -1, that is a contradiction. As a result,
(2x-1)/(1-x) cant be equal to -2.

I hope this works for you!

User Delante Lee Bess
by
5.8k points